Optobiology: optical control of biological processes via protein engineering. (23rd September 2013) - Kim, Benjamin; Lin, Michael Z.
Abstract : Enabling optical control over biological processes is a defining goal of the new field of optogenetics. Control of membrane voltage by natural rhodopsin family ion channels has found widespread acceptance in neuroscience, due to the fact that these natural proteins control membrane voltage without further engineering. In contrast, optical control of intracellular biological processes has been a fragmented effort, with various laboratories engineering light-responsive properties into proteins in different manners. In the present article, we review the various systems that have been developed for controlling protein functions with light based on vertebrate rhodopsins, plant photoregulatory proteins and, most recently, the photoswitchable fluorescent protein Dronpa. By allowing biology to be controlled with spatiotemporal specificity and tunable dynamics, light-controllable proteins will find applications in the understanding of cellular and organismal biology and in synthetic biology.